Quantitative proteomics revealed novel proteins associated with molecular subtypes of breast cancer - Suman, Shankar; Basak, Trayambak; Gupta, Prachi; Mishra, Sanjay; Kumar, Vijay; Sengupta, Shantanu; Shukla, Yogeshwer (Journal of proteomics, 2016)
The early diagnosis and successful treatment of breast cancer (BC) is still a challenging task due to the diverse origin and functional heterogeneity of cancer cells. The heterogeneity of BC may likely to explained by molecular BC subtypes, comprises Luminal-A (LA), Luminal-B (LB), Triple-negative (TN) and HER2-positive (HP), which are governed by a variety of cancer associated pathways. To identify protein signatures in different BC subtypes, we performed isobaric tag for absolute and relative quantitation (iTRAQ) of enriched blood plasma samples of BC subtypes (N=32) and healthy subjects (N=8). After analyses of data, 58 proteins were found to be modulated in BC subtypes from healthy subjects (p<0.05) and among these; Fibronectin (FN1), Alpha-2-macroglobulin (A2M), and Complement component-4-binding protein-alpha (C4BPA) and Complement factor-B (CFB) were selected for validation in BC subtypes and healthy subjects in the independent set of blood plasma (N=100) and tissue samples (N=25). Statistical analysis showed the significant modulation of FN1 and C4BPA in LB, and A2M in TN patients in both plasma as well as tissues comparatively control (p<0.05). Further, FN1 and C4BPA in LB subtype revealed a good diagnostic accuracy in plasma level validation. The receiver operating characteristic (ROC) curve and regression analysis demonstrated that these proteins with associated criterion of expression could act as discriminating signatures among BC subtypes with diagnostic and prognostic relevance. The heterogeneity of breast cancer (BC) has gained many challenges for successful management of BC, thus, the delineating proteomic alterations BC subtypes may provide great clinical values in diagnostic, prognostic and therapeutics of BC. The findings from the present quantitative proteomic study have deciphered the altered proteomic patterns and their possible molecular interactions in each BC subtype. The study showed a strong association of FN1, A2M, C4BPA and CFB in molecular subtypes of BC, in which, C4BPA and A2M demonstrated a potent signature in blood plasma and tissue samples of LB and TN subtypes in BC patients, respectively. The findings also revealed the altered level expressions of these selected proteins could classify BC subtypes through plasma and tissue based expression analysis in patients and control samples. Hence, these proteins could have clinical importance for the diagnosis and prognosis purposes among molecular BC subtypes. [Display omitted] •Quantitative proteomics performed for the identification of protein signatures in BC subtypes.•< 1% FDR, 58 proteins were modulated in BC subtypes from healthy subjects taking >1.5 fold change and >2 peptide hits.•Protein network pathways were mapped in each of BC subtypes.•FN1, A2M, C4BPA and CFB showed discriminating signatures with associated criterion of expression in BC subtypes.•Altered expression of CFB in LA, FN1 & C4BPA in LB and HP and A2M in TN subtypes revealed a good diagnostic accuracy.